Functional Analysis of MAX2 in Phototropins-Mediated Cotyledon Flattening in Arabidopsis - Zhao, Qing-Ping; Wang, Xiao-Nan; Li, Nan-Nan; Zhu, Zi-Yi; Mu, Shi-Chao; Zhao, Xiang; Zhang, Xiao (Frontiers in Plant Science, 2018)
Phototropins (phot1 and phot2) are blue-light receptors that control cotyledon flattening and positioning under strong light; however, their functional redundancy restricts our understanding of the specific roles of phot2. To identify the factors responsible for phot2-dependent cotyledon flattening and growth, we screened for light-insensitive mutants among mutagenized phot1 mutants in Arabidopsis thaliana. The mutant of a putative phot2 regulator, lea1 (leaf expansion associated 1), is defective in cotyledon flattening and positioning but not the phototropic response. This mutant phenotype could be alleviated by constitutively expressing MORE AXILLARY GROWTH 2 (MAX2), indicating that LEA1 was allelic to MAX2. The max2 mutants (max2-2 and max2-3) are defective in cotyledon flattening, which is similar to that of the phot1 phot2 mutants. Moreover, the amounts of MAX2 transcripts are inhibited in leaves of phot1 mutant. However, the additional disruption of PHOT1 gene in max2-2 or max2-3 did not affect their phenotype, including MAX2-mediated inhibition of hypocotyl elongation. By contrast, phototropins-mediated hypocotyl phototropism was not regulated by MAX2. Together, these results suggest that phototropins-mediated cotyledon flattening depends on MAX2, but they mediated hypocotyl phototropism does not depend on MAX2.